Andrew Stevenson and J.W. Stevenson papers - Stevenson, Andrew, 1784-1857.; Stevenson, J. W. (John White), 1812-1886.
Correspondence, speeches, legal records, account book, printed matter, and other papers of Andrew Stevenson and his son, J.W. Stevenson.
Papers of Andrew Stevenson document his service as U.S. minister to Great Britain and relate primarily to U.S. foreign relations with Great Britain. Subjects include the Caroline affair (1837-1838), negotiations for the settlement of the northeastern boundary between the U.S. and Canada, and the ascendancy of Victoria, Queen of Great Britain. Also includes material pertaining to his service in the U.S. House of Representatives and to lawsuits in Virginia courts, an autograph poem of William Wordsworth, a poem by Thomas Moore, and a letter (1827 Jan. 29) of Robert Southey to John Kenyon transmitting a portion of Southey's poem "The Devil's Visit." Correspondents include James Buchanan; John C. Calhoun; Churchill Caldum Cambreleng; Lewis Cass; Edward Everett; John Forsyth; Francis Scott Key; William L. Marcy; Philip Norborne Nicholas; Henry John Temple, Viscount Palmerston; Joel Roberts Poinsett; James K. Polk; Thomas Ritchie; William C. Rives; Benjamin Rush; Richard Rush; John Russell, Earl Russell; John Rutherfoord; Sarah Coles Stevenson; Charles Sumner; Roger Brooke Taney; George Tucker; Martin Van Buren; Alexander Van Rensselaer; and Daniel Webster.
Papers of J.W. Stevenson consist principally of correspondence kept while governor of and U.S. senator from Kentucky. His correspondents include John C. Breckinridge, John Griffin Carlisle, Leslie Combs, C.M. Ingersoll, and Richard Vaux.
Andrew Stevenson (1785-1857), U.S. representative from Virginia, speaker of the House of Representatives, and minister to Great Britain; and his son, J.W. (John White) Stevenson, governor of and U.S. senator from Kentucky.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Card index for the bulk of the collection available in the Library of Congress Manuscript Reading Room.
Keywords: Breckinridge, John C. -- 1821-1875 -- Correspondence; Buchanan, James, -- 1791-1868 -- Correspondence; Calhoun, John C. -- 1782-1850 -- Correspondence; Cambreleng, Churchill Caldom, -- 1786-1862 -- Correspondence; Carlisle, John Griffin, -- 1835-1910 -- Correspondence; Cass, Lewis, -- 1782-1866 -- Correspondence; Combs, Leslie, -- 1793-1881 -- Correspondence; Everett, Edward, -- 1794-1865 -- Correspondence; Forsyth, John, -- 1780-1841 -- Correspondence; Ingersoll, C. M. -- 1819-1904 -- Correspondence; Kenyon, John, -- 1784-1856 -- Correspondence; Key, Francis Scott, -- 1779-1843 -- Correspondence; Marcy, William L. -- 1786-1857 -- Correspondence; Moore, Thomas, -- 1779-1852 -- Poetry; Nicholas, Philip Norborne, -- 1775?-1849 -- Correspondence; Palmerston, Henry John Temple, -- Viscount, -- 1784-1865 -- Correspondence; Poinsett, Joel Roberts, -- 1779-1851 -- Correspondence; Polk, James K. -- 1795-1849 -- Correspondence; Ritchie, Thomas, -- 1778-1854 -- Correspondence; Rives, William C. -- 1793-1868 -- Correspondence; Rush, Benjamin, -- 1746-1813 -- Correspondence; Rush, Richard, -- 1780-1859 -- Correspondence; Rutherfoord, John, -- 1792-1866 -- Correspondence; Russell, John Russell, -- Earl, -- 1792-1878 -- Correspondence; Southey, Robert, -- 1774-1843 -- Correspondence; Southey, Robert, -- 1774-1843 -- Poetry; Stevenson, Sarah Coles, -- 1789-1848 -- Correspondence; Sumner, Charles, -- 1811-1874 -- Correspondence; Taney, Roger Brooke, -- 1777-1864 -- Correspondence; Tucker, George, -- 1775-1861 -- Correspondence; Van Buren, Martin, -- 1782-1862 -- Correspondence; Van Rensselaer, Alexander -- Correspondence; Vaux, Richard, -- 1816-1895 -- Correspondence; Victoria, -- Queen of Great Britain, -- 1819-1901.; Webster, Daniel, -- 1782-1852 -- Correspondence; Wordsworth, William, -- 1770-1850 -- Poetry; Actions and defenses -- Virginia; Diplomatic and consular service, American -- Great Britain; Poetry; Slave trade; Canada -- Boundaries -- United States; Great Britain -- Foreign relations -- United States; Kentucky -- Politics and government; United States -- Boundaries -- Canada; United States -- Foreign relations -- Great Britain; United States -- Politics and government -- 19th century; Diplomats; Governors -- Kentucky; Representatives, U.S. Congress -- Virginia; Senators, U.S. Congress -- Kentucky; Speakers of the House, U.S. Congress